Uji Sitotoksik Ekstrak dan Fraksi Daun Jati (Tectona Grandis Linn. F.) dengan Metoda Brine Shrimp Lethality Bioassay - Alen, Yohannes; Akhsanita, Mardha; mulyani, Isna; Susanti, Meri (Fakultas Farmasi Universitas Andalas, 2012)
he Study of cytotoxic effects of the methanolic extract and the fraction of Teakâs leave (Tectona grandis Linn. f.) by using Brine Shrimp Lethality Bioassay Method had been done. Results showed that the methanolic extract have cytotoxic level of (LC50) 16,58 ppm, n-hexane fraction 21,83 ppm, ethyl acetate fraction 21,31 ppm and residue fraction 21,27 ppm, respectively.